Investigation of the stability on boring tool attached with double impact dampers using Taguchi based Grey analysis and cutting tool temperature investigation through FLUKE-Thermal imager. (January 2019) - Ramesh, K.; Baranitharan, P.; Sakthivel, R.
Highlights: Boring tool vibration has been reduced by attaching impact copper dampers in tool. Cutting tool wear is minimized via reducing tool vibration. Optimizing the boring tool machining process parameters. Taguchi based Grey analysis is used to optimize the machining characteristics. Correlation between tool wear and tool temperature was studied by thermal imaging. Abstract: This article focuses on the investigation of machining characteristics of double impact dampers attached with boring tool and grey relational analysis (GRA) based multi-objective optimization for lower tool wear and better cutting force. Taguchi based orthogonal array method was exploited to formulate the experimental plan for the boring operation. Considering impact damper positions, speed and depth of cut as the input control factors, the output responses such as cutting force and tool wear were obtained from the L27 orthogonal array. ANOVA results exposed that damper position and speed had more effect on tool wear and cutting force respectively than depth of cut. Based on the obtained output response for cutting force and tool wear a comprehensive mathematical model was developed. The developed mathematical model for tool wear and cutting force predicted values similar to that of experimental results. The obtained result was corroborated clinched Fluke thermal image analyzer. Thermal imaging result showed that the optimized cutting conditions gives low tool temperature there by reduced tool wear can be obtained. Multi-objective criteria optimization was done through GRA technique and the recommended optimum parameters set provides better cutting force (Cf) of 342.47 N and less tool wear (Tw) of 0.22 mm.